Numerical study for slip flow of Reiner-Rivlin nanofluid due to a rotating disk. (July 2020) - Raza Shah Naqvi, Syed Muhammad; Kim, Hyun Min; Muhammad, Taseer; Mallawi, Fouad; Ullah, Malik Zaka
Abstract: The analysis of heat augmentation through non-Newtonian fluid is found promising and suitable arena for technological applications than the Newtonian fluid. Herein, a new kind of non-Newtonian (Reiner-Rivlin) fluid has been examined by a rough rotating disk under various slip conditions. A coupled nonlinear differential system is obtained due to constitutive relations in Reiner-Rivlin liquid. An advantageous numerical treatment is summoned to explain the subsequent similitude conditions for wide scopes of non-Newtonian liquid parameter and slip coefficients. Our principle here is to foresee the von-Kármán flow problem under the practices of liquid viscosity and wall slip coefficients. From our calculations, it is found that to keep consistent rotation of disk we need higher torque when wall slip is high. For wide range of parameters calculations are made for surface heat transfer and wall skin friction.